Peran Guru PAI dalam Mengatasi Kesulitan Membaca Al-Qur’an di SMP Islam Arraudhoh - Muhammad Arifin Rahmanto; Adeliyah Khairul (Universitas Muhammadiyah Prof Dr Hamka, 2022)
This study was conducted to describe the role of PAI teachers in overcoming difficulties in reading the Qur'an at Arraudhoh Islamic Middle School. PAI teachers have a very important role in learning the Qur'an, therefore PAI teachers must pay attention to students in particular to give more attention to students who are still have difficulty in reading the Qur'an. This research is a descriptive qualitative research, and the data collection tools used are observation, in-depth interviews, and documentation. Informants in this study were PAI teachers and students who were selected for in-depth interviews with the aim of obtaining the information needed in this study. From the results of the study, it was found that there were around 15 students from 49 students who still had difficulty reading the Qur'an in class IX of Arraudhoh Islamic Middle School, and PAI teachers had done their best. such as, the habit of reading the Qur'an before starting learning, collaborating with other teachers, holding additional lessons on reading the Qur'an after school, and also using the Iqra teaching method, lectures, classical and private in learning.